Delimitation Issues of Internal Waters in Indonesia: Asserting Historic Title Under International Law - Tsany Ariqah Tsabitah; Davina Oktivana (Greenation Research & Yayasan Global Resarch National, 2026)
Internal waters represent a vital maritime domain through which a State exercises sovereignty and ensures national security. However, their delimitation remains complex, particularly when intersecting with claims of historic title under international law. This study examines Indonesia’s authority, as an archipelagic State under Article 50 of the United Nations Convention on the Law of the Sea 1982, to designate Tomini Bay as a historic bay. Employing a normative legal method with a comparative approach, the research analyzes the legal framework governing internal waters, historic title, and relevant State practice. It further explores the legal implications of reclassifying Tomini Bay from archipelagic waters to internal waters. The findings highlight that such a designation requires strict adherence to customary international law criteria and may significantly affect sovereignty claims, navigational rights, and international recognition.